Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1159/000236083
|View full text |Cite
|
Sign up to set email alerts
|

Growth Monitoring to Detect Children with Cystic Fibrosis

Abstract: Background/Aims: Cystic fibrosis (CF) in infancy and childhood is often associated with failure to thrive (FTT). This would suggest that in countries without a newborn screening program for CF, FTT could be used as a clinical screening tool. The aim of this study is to assess the diagnostic performance of FTT for identifying children with CF. Methods: Longitudinal length and weight measurements up to 2.5 years of age were used from CF patients (n = 123) and a reference group (n = 2,151) in The Netherlands. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 64 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…The results from this study showed that the most common manifestation at first admission was FTT, which is also considered as the earliest feature of CF in infants diagnosed by neonatal screening (17). This would suggest that in countries without a newborn screening program, FTT could be used as a clinical screening tool (17).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The results from this study showed that the most common manifestation at first admission was FTT, which is also considered as the earliest feature of CF in infants diagnosed by neonatal screening (17). This would suggest that in countries without a newborn screening program, FTT could be used as a clinical screening tool (17).…”
Section: Discussionmentioning
confidence: 77%
“…In regions without newborn screening, clinical screening tools for identification of potential patients to consider for SCT would be very useful (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of children who complied with the decision rule that proved most effective for celiac disease and cystic fibrosis (combining BMI SDS of ! -2 and change in BMI of 1 0.5/year) [2,3] was 7/9.…”
Section: Weight For Age and Bmimentioning
confidence: 93%
“…We have also tested this guideline for its effectiveness in detecting celiac disease and cystic fibrosis, which showed that the change in body mass index is a better marker to detect both conditions, although the sensitivity is still low (approximately 30%) [2,3] .…”
Section: Introductionmentioning
confidence: 99%